Pro-arrhythmic Effects of Hydrogen Sulfide in Healthy and Ischemic Cardiac Tissues: Insight From a Simulation Study - Zhang, Shugang; Zhang, Shanzhuo; Fan, Xiaoshuai; Wang, Wei; Li, Zhen; Jia, Dongning; Wei, Zhiqiang; Zhang, Henggui (Frontiers in Physiology, 2019)
H2S, an ambient air pollutant, has been reported to increase cardiac events in patients with cardiovascular diseases, but the underlying mechanism(s) remain not elucidated. This study investigated the pro-arrhythmic effects of H2S in healthy and ischemic conditions. Experimental data of H2S effects on ionic channels (including the L-type Ca2+ channel and ATP sensitive K+ channel) were incorporated into a virtual heart model to evaluate their integral action on cardiac arrhythmogenesis. It was shown that H2S depressed cellular excitability, abbreviated action potential duration, augmented tissue’s transmural dispersion of repolarization, resulting in an increased tissue’s susceptibility to initiation and maintenance of reentry. The observed effects of H2S on cardiac excitation are more remarkable in the ischemic condition than in the healthy condition. This study provides mechanistic insights into the pro-arrhythmic effects of air pollution (H2S), especially in the case with extant ischemic conditions.